2020
DOI: 10.1002/aqc.3280
|View full text |Cite
|
Sign up to set email alerts
|

Food risk trade‐off in the Indo‐Pacific humpback dolphin: An exploratory case study

Abstract: 1. Based on optimal foraging theory, animals are expected to maximize foraging benefits whilst minimizing risks. Despite risking being subjected to anthropogenic impacts such as water contamination, marine traffic, and underwater noise, estuaries have been identified as the preferred habitat of the Indo-Pacific humpback dolphin (Sousa chinensis, IPHD). However, it remains unclear why this vulnerable species favours such risky habitats. 2.Here, an exploratory case study in Zhanjiang estuary, China, was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(60 reference statements)
0
5
1
Order By: Relevance
“…The authors observed a significant relationship between detection rates of anthropogenic sounds and dolphin sounds; however, fish detection rates showed no effect on dolphin detection rates. These findings indicated anthropogenic activity avoidance and no forced foraging in humpback dolphins in the study area, which differed from observations in other waters (Pine et al 2017;Lin et al 2020).…”
Section: Underwater Soundscape and Bioacoustic Behaviorcontrasting
confidence: 88%
“…The authors observed a significant relationship between detection rates of anthropogenic sounds and dolphin sounds; however, fish detection rates showed no effect on dolphin detection rates. These findings indicated anthropogenic activity avoidance and no forced foraging in humpback dolphins in the study area, which differed from observations in other waters (Pine et al 2017;Lin et al 2020).…”
Section: Underwater Soundscape and Bioacoustic Behaviorcontrasting
confidence: 88%
“…• The present findings provide some indications of general 'hotspot areas' of humpback dolphin distribution; however, a more in-depth assessment is needed to accurately indicate distribution boundaries and priority areas for place-based conservation (Liu et al, 2020;Lin et al, 2021). Specific investigations are urgently required, particularly for some poorly investigated populations, such as those in SWH, ST and ND.…”
Section: Conclusion Conservation Implications and Suggestionsmentioning
confidence: 84%
“…Guangdong‐Hong Kong‐Macao Greater Bay Area; Karczmarski et al, 2016), the Indus River Delta (Kiani & Van Waerebeek, 2015; Sutaria et al, 2015), the Gulf of Thailand (Jutapruet et al, 2015) and the Bay of Bengal coast (Amaral et al, 2020), where human activities pose increased disturbances and pressures to marine megafauna. Consequently, humpback dolphins are extremely vulnerable to a variety of human‐caused survival threats, such as fishery bycatch (Atkins, Cliff & Pillay, 2013; Liu et al, 2017a; Wang et al, 2018; Wu et al, 2022), habitat loss/degradation (Karczmarski et al, 2017; Wang et al, 2017; Wu et al, 2017; Huang et al, 2022) and maritime traffic (Li et al, 2015; Liu et al, 2017b; Li et al, 2018; Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Species-specific identification of the sounds produced by dolphins was not applied in this work. We supposed that the majority of these sounds were produced by IPHD, considering that IPHD is the only dominant dolphin species recorded during our long-term periodical boat-based visual surveys (started in 2013) and local ecological knowledge (LEK) survey in the investigated waters [ 62 ], with other dolphin species (i.e., the Indo-Pacific bottlenose dolphin) emitting similar sounds of IPHD were sighted only once, which was in the northernmost part of the investigated waters. Besides, up to six types of sounds from soniferous fishes were found, on which the species-specific identification was not applied.…”
Section: Resultsmentioning
confidence: 99%
“…Species-specific identification of the sounds produced by dolphins was not applied in this work. We supposed that the majority of these sounds were produced by IPHD, considering that IPHD is the only dominant dolphin species recorded during our long-term periodical boat-based visual surveys (started in 2013) and local ecological knowledge (LEK) survey in the investigated waters [62], with other dolphin species…”
Section: Main Biological and Anthropogenic Sound Sourcesmentioning
confidence: 99%